Ameliorative effect of liquorice extract versus silymarin in experimentally induced chronic hepatitis: A biochemical and genetical study. (February 2019) - Abdel Maksoud, H.A.; Abdel Magid, Afaf D.; Mostafa, Y.M.; Elharrif, Mohamed G.; Sorour, Reem I.; Sorour, Mohammed Ibrahim
Summary: Chronic hepatitis is major health problem that affect liver function with high morbidity and mortality in developing countries. Macerated liquorice root used since several decades as one of traditional drink in Egypt. We aimed in this study to evaluate the hepatoprotective effect of liquorice extract versus silymarin in chronic hepatitis rat model and explain the possible mechanism of hepatoprotection in such disease. To achieve our aim fifty male albino rats were used and divided into 5 equal groups, control group, chronic hepatitis group, chronic hepatitis group protected with liquorice extract, chronic hepatitis group protected with silymarin, normal group administrated liquorice extract. The results of the study exhibits the hepatoprotective effects of liquorice extract against chronic hepatitis as well as silymarin through there antiinflammatory and antioxidants mechanism.